Facile synthesis of nanostructured carbon materials over RANEY® nickel catalyst films printed on Al2O3 and SiO2 substrates1. Issue 8 (28th February 2015) - Lin, Jhih-Fong; Mohl, Melinda; Nelo, Mikko; Toth, Geza; Kukovecz, Ákos; Kónya, Zoltán; Sridhar, Srividya; Vajtai, Robert; Ajayan, Pulickel M.; Su, Wei-Fang; Jantunen, Heli; Kordas, Krisztian
<x xml:space="preserve">Abstract</x> Films of porous RANEY® Ni catalyst particles deposited on substrates by stencil printing offer a facile platform for synthesizing nanostructured carbon/nickel composites for direct use as electrodes in electrochemical and field emitter devices.